2009
DOI: 10.1186/1471-2202-10-111
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of transgenic expression of porcine heat shock protein 70 on hypothalamic ischemic and oxidative damage in a mouse model of heatstroke

Abstract: Background: Transgenic mice have been used to examine the role of heat shock protein (HSP)72 in experimental heatstroke. Transgenic mice that were heterozygous for a porcine HSP70β gene ([+] HSP72) and transgene-negative littermate controls ([-] HSP72), under pentobarbital sodium anesthesia, were subjected to heat stress to induce heatstroke. It was found that the overexpression of HSP72 in multiple organs improved survival during heatstroke by reducing hypotension and cerebral ischemia and damage in mice. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 37 publications
3
30
0
1
Order By: Relevance
“…Recent research has demonstrated that Hsp27 and Hsp70 have protective effects in cerebral I/R injury (29,30). In the present study, we also observed that Hsp27 and Hsp70 levels were significantly increased in the poly(I:C) group.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Recent research has demonstrated that Hsp27 and Hsp70 have protective effects in cerebral I/R injury (29,30). In the present study, we also observed that Hsp27 and Hsp70 levels were significantly increased in the poly(I:C) group.…”
Section: Discussionsupporting
confidence: 77%
“…1B). Recent studies have shown that Hsp27 and Hsp70 have protective effects against cerebral I/R injury (29,30). Our results also showed that poly(I:C) significantly increased the levels of Hsp27 ( Fig.…”
Section: Flow Cytometrysupporting
confidence: 77%
“…Hyperthermia is a limiting factor in physical performance [21]; therefore, upregulation of genes encoding HSPs and interleukins could be essential for gaining thermotolerance [22]. There are not many reports in the literature on changes in gene expression upon one-off Finnish sauna bath that would include people who train regularly and those who do not exhibit regular physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the new mass spectroscopic technique MALDI MS revealed the changes of phospholipids, such as lysophosphatidylcholine, phosphatidylcholine, phosphatidylethanolamine, and sphingomyelin, in rat brains after focal cerebral ischemia (26). Studies have revealed that inducible Hsp70.1 has protective effects against ischemia and oxidative injury (27,28); however, whether its protection correlates with membrane lipids remains to be elucidated. A recent study has demonstrated that Hsp70 selectively interacts with the negatively charged phospholipids, such as cardiolipin (CL), phosphatidylserine (PS), and BMP.…”
Section: Journal Of Biological Chemistry 27439mentioning
confidence: 99%